ISLAM DAN EKONOMI - Efyanti, Yasni (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2015)
Repeating the process of fulfilling human needs makes humans can identify, classify and verify the behavior patterns that are more effective in fulfilling the needs of his life. In Islam all phenomena in this life is a situation that led humans to further recognize the greatness of God. how Islam sees about human activities in fulfilling the needs in terms of economic concepts. Syariat is a reference to the actions of Muslims in religious then it is closely related to the problem of faith, worship and muammalah. The purpose of shariah; in Islam is to achieve the benefit of servants, both the world and the hereafter. The benefit is based on five grounds, namely: Maintaining Religion-hifh ad-Din, soul-hifdh Maintaining an-nafs, Maintaining sense - hifzh al-aql, Maintaining, hifzh an-nas, wealth Maintaining hifzh mall. some economic policies based on the principles of the Quran is as follows: Allah is the absolute supreme ruler and owner of the entire universe, man is only the caliph of God on earth, not the actual owner, all owned and acquired by humans is the permission of Allah, therefore people who are less fortunate have a right of share of the wealth of people who are rich, more fortunate, Wealth must spin and should not be dumped, Economic exploitation in all its forms, including usury should be eliminated, Applying systems legacy as a redistribution of wealth, stipulate an obligation for all individuals, including for the poorÂ Proses yang berulang dari pemenuhan kebutuhan manusia menjadikan manusia dapat mengidentifikasi, mengklasifikasi dan memverifikasi pola perilaku yang lebih efektif dalam memenuhi kebutuhan hidup. Dalam Islam semua fenomena dalam kehidupan ini merupakan suatu keadaan yang mengantar manusia untuk bisa lebih jauh mengenal kebesaran Allah. Islam melihat aktifitas manusia dalam memenuhi kebutuhan konsep ekonomi. Syariat itu merupakan rujukan tindakan umat Islam dalam beragama, erat kaitannya dengan masalah akidah, ibadah dan muammalah. Adapun tujuan syari;at Islam adalah mencapai kemaslahatan hamba. Kemaslahatan tersebut didasarkan pada lima dasar, yakni: Memelihara Agama-hifh ad-Din,Memelihara jiwa-hifdh an-Nafs,Memelihara akal â hifzh al-aql, Memelihara keturunhlan â hifzh an-nas, Memelihara kekayaan- hifzh mal. beberapa kebijakan ekonomi berdasarkan prinsip-prinsip al-Qurâan adalah sebagai berikut:Allah swt adalah penguasa tertinggi sekaligus pemilik absolute seluruh alam semesta, Semua yang dimiliki dan yang didapatkan oleh manusia adalah seizin Allah, oleh karenanya manusia yang kurang beruntung mempunyai hak atas sebagian kekayaan yang dimiliki manusia lain yang lebih beruntung, Kekayaan harus berputar dan tidak boleh ditimbun, Eksploitasi ekonomi dalam segala bentuknya, termasuk riba harus dihilangkan, Menerapkan system warisan sebagai redistribusi kekayaan, Menetapkan kewajiban bagi seluruh individu, termasuk bagi orang-orang miskin.